2008
DOI: 10.1111/j.1473-6861.2008.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Student nurse transition from traditional to problem‐based learning

Abstract: Problem-based learning (PBL) continues to be a feature of many nursing programmes and has been the subject of a number of empirical studies. This study explored the experience of PBL of a group of registered nurses undertaking a 1 year children's nursing programme. Focus group interviews at the end of the programme and 6 months post-qualification captured the student's perceptions of how they experienced learning to be a children's nurse on this type of programme and subsequently the impact it had had on them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…The results of this study provide further evidence regarding the effectiveness of utilizing CM and PBL to stimulate critical thinking during care plan development. Prior research examining critical thinking, CM, and PBL have reported similar results (Atay & Karabacak, 2012;Huang et al, 2012;Kocaman et al, 2009;Lin et al, 2010;Moattari et al, 2014;Ozturk et al, 2008;Smith & Coleman, 2008;Taylor & Wros, 2007). Although repeated experiences may have contributed to improved care plan development, previous studies evaluating critical thinking using a pretest-posttest design have demonstrated similar fi ndings (Atay & Karabacak, 2012;Wilgis & McConnell, 2008;Yuan et al, 2008).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The results of this study provide further evidence regarding the effectiveness of utilizing CM and PBL to stimulate critical thinking during care plan development. Prior research examining critical thinking, CM, and PBL have reported similar results (Atay & Karabacak, 2012;Huang et al, 2012;Kocaman et al, 2009;Lin et al, 2010;Moattari et al, 2014;Ozturk et al, 2008;Smith & Coleman, 2008;Taylor & Wros, 2007). Although repeated experiences may have contributed to improved care plan development, previous studies evaluating critical thinking using a pretest-posttest design have demonstrated similar fi ndings (Atay & Karabacak, 2012;Wilgis & McConnell, 2008;Yuan et al, 2008).…”
Section: Discussionmentioning
confidence: 67%
“…Five steps form the basic process of PBL: (a) review the case, (b) analyze actual or potential health issues, (c) identify knowledge gaps, (d) conduct research, and (e) develop an action plan. Prior research that investigated PBL reported increased engagement, self-direction, satisfaction, motivation, and autonomy (Hwang & Kim, 2006;Lin, Lu, Chung, & Yang, 2010;Ozturk, Muslu, & Dicle, 2008;Smith & Coleman, 2008;Tiwari, Lai, So, & Yuen, 2006;Yuan et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 97%
“…This study finding reflects findings about returning RNs who felt their past experiences were not recognized. [48] The Bilingual students shared similar characteristics with the Collaborative students in that they wanted more direction and feedback about their learning. [48] Even though the students received minimal lecture from the tutors, the tutors provided direction to the students in accordance with the CBL philosophy of learning.…”
Section: Discussionmentioning
confidence: 95%
“…[48] The Bilingual students shared similar characteristics with the Collaborative students in that they wanted more direction and feedback about their learning. [48] Even though the students received minimal lecture from the tutors, the tutors provided direction to the students in accordance with the CBL philosophy of learning. The researcher recommends that at orientation, the philosophy of the CBL curriculum, including the belief that knowledge is socially formed through interaction with peers, is discussed and any possible misconceptions are clarified in order to reduce the anxiety linked with transition to CBL program.…”
Section: Discussionmentioning
confidence: 95%
“…Each module incorporated a hybrid method, with PBL interspersed with didactic sessions (Smith & Coleman 2008). The content of both approaches directly related to the learning outcomes of the module.…”
mentioning
confidence: 99%